3A + 9B = 3(A + 3B)
There are 3 terms in the given expression of 6a+9b+15
The simplified expression is -9a -9b.
-28am + 17b
3a + 5b - 6a - 9b = -3a - 4b
9b + 6 - 8 = -36 9b = -38 b = 4.2222222(repeating)
You would factor 3a + 9b as: 3(a+3b)
2a + 3 - 9b - a - 7 Bring like terms together: = 2a - a - 9b + 3 - 7 Combine like terms: = a - 9b - 4
(6ab + 9b)/(2a + 3) = 3b(2a + 3)/(2a + 3) = 3b
There are three terms in the given expression.
(27a)2 = 729a2 (9b)3 = 729b3 So (27a)2 + (9b)3 = 729*(a2 + b3)
When simplified it is: 2a+8b+4
It is not an equation but an algebraic expression that can be simplified to: 12b-5a
(2b - 5)(b + 7)
Since 3b is a factor of 9b, it is automatically the GCF.
15b+2-13 = 13b+6-4b 15b-11 = 9b+6 15b-9b = 6+11 6b = 17 b =17/6 or 2 and 5/6
8b^2 -9b +1 8b^2 -8b -b +1 8b(b-1) - 1(b-1) (8b-1)(b-1)
What I would do is change the problem up. Instead of b-9b I would make it -(9b-b). It is still the same problem; you will multiply the number inside the parenthesis be -1. So start with 9b-b. That would equal 8b. So it would change from -(9b-b) to -(8b) so you multiply 8b by negative 1 (-1) to get the answer -8b. -8b is your answer. So b - 9b = -8b
All the terms in b add to 11, so 11b = 132 making b = 12